Pharmacological effect of aminoferrocene in mice with L1210 leukemia - Chekhun, V.F.; Mokhir, A.; Daum, S.; Todor, I.N.; Lukianova, N.Yu.; Shvets, Yu.V.; Burlaka, A.P. (Experimental Oncology, 2015)
Aim: To study the cytostatic and some biological effects of aminoferrocene using mice with L1210 lymphoid leukemia. Materials and Methods: Experiments were performed on BDF1 male mice (DBA/2, female × C57Bl/6, male) with transplantable L1210 lymphoid leukemia. Determination of antitumor activity of Benzyl-Fc Boron (Bn), it was injected intraperitoneally 6 times daily, starting on day 2 after L1210 leukemia cell transplantation. Doses of Bn such as 26; 260 and 2600 μg/kg were used. The determination of intracellular content of cardiolipin, thiols, reactive oxygen species (ROS) and also analysis of Annexin V positivity and mitochondrial transmembrane potential (JC-1 staining) were performed with use of flow cytometry. The levels of “free iron” complexes, transferrin active forms and the rate of NO generation were measured by EPR-specroscopy. Results: Six daily injections of Bn at a dose of 26 μg/kg resulted in an increased survival of mice with L1210 leukemia by 28% (p < 0.05). Bn led to an increase of apoptotic cells number and ROS amount in leukemia cells. Besides, Bn caused a decrease of cardiolipin and nonprotein thiol compounds content. The membrane electrochemical potential of cell mitochondria was decreased also after Bn administration. Studies using EPR-spectroscopy revealed a significant increase in a level of “free iron”, content of transferrin active species and generation rate of NO by inducible NO-synthase in L1210 cells after aminoferrocene administration. Conclusion: Our data indicate that Benzyl-Fc Boron can be promising candidate for realizing a new strategy of anticancer therapy with the use of ROS-inducing agents. Key Words: aminoferrocene, tumor, L1210 leukemia, mitochondria membrane electrochemical potential, cardiolipin, thiols, ROS, transferrin, NO-generation.